NGOs and their impact on the adoption of technologies: Case of cocoa producers in the Quinsaloma canton, Ecuador - Simba Ochoa, Luis Fernando (2018)
The study was carried out in Quinsaloma canton, Los Ríos province, Ecuador, in order to determine the level of adoption of technology in cocoa cultivation. 68 beneficiaries of three ONGs were surveyed [(ADVI-VOCA (25), MCCH (22), ANECACAO (21)] and 27 producers that they do not receive TA, applying a simple random sampling, considering the farmers that in their properties have national cocoa (CN) and Castro Naranjal Collection (CCN-51) and whose plantation age is homogeneous. The data were tabulated by SPSS version 13. It was established that ONGs used various training and accompaniment strategies until post-harvest and commercialization The greatest increase in productivity for CN was found in the producers advised by ACDI-VOCA (105.56%), and for CCN-51 those advised by ANECACAO (189.74%), when comparing the productivity of the CN and CCN-51 of the farmers who received TA in relation to those who did not receive, in the case of the CN. It was 42.31%, 33.33% and 48.72% and for CCN-51 it was 105.74%, 140.47% and 159.77% for each NGO respectively. Higher Profitability was obtained by farmers cattle that received AT from ANECACO with 60.64% (CN) and 130.08% (CCN-51). The economic surplus of the increase in the area grown are the production was greater than 50% with positive displacement of the supply curve and the last one, the impact on productivity is also positive since the average increase in production was 100.11 percent.